Balinese textile:inclusive reflection on culture and Hindu religion. - Tjok Istri Ratna, Cora Sudharsana (2017)
The Hindu religion in Bali is closely related to Balinese culture.One of them is the relation between arts and Hindu's rituals.Almost all of rituals processions require medium of textiles,whether used by ritual participants,dancers,or used as sacred wrappers for sculptures and trees that are considered sacred.The type of textile based on its position,can be divided into three groups,namely:magical textiles,grandeur textiles,and decorative textiles.In general,Balinese textile pattern are geometric and organic that inspired by flora,fauna and wayang (puppets).This pattern can be developed except for pattern on textiles that are classified as magical textiles.While the color of Balinese textiles consists of various colors,almost all colors can be used in textile-making.Author inspired by characteristic of Balinese textile and using painting techniques to make new textile that can be used as part of the Balinese rituals,temple also sacred statue and trees wrappers and many more.Become part of the author's dissertation.The stage of creation this new textile has been summarized into the Creation Method "Frangipani".